The mTORC1/eIF4E/HIF-1α Pathway Mediates Glycolysis to Support Brain Hypoxia Resistance in the Gansu Zokor, Eospalax cansus - Lin, Jinyan; Fan, Lele; Han, Yuming; Guo, Juanjuan; Hao, Zhiqiang; Cao, Lingna; Kang, Jiamin; Wang, Xiaoqin; He, Jianping; Li, Jingang (Frontiers in Physiology, 2021)
The Gansu zokor (Eospalax cansus) is a subterranean rodent species that is unique to China. These creatures inhabit underground burrows with a hypoxia environment. Metabolic energy patterns in subterranean rodents have become a recent focus of research; however, little is known about brain energy metabolism under conditions of hypoxia in this species. The mammalian (mechanistic) target of rapamycin complex 1 (mTORC1) coordinates eukaryotic cell growth and metabolism, and its downstream targets regulate hypoxia inducible factor-1α (HIF-1α) under conditions of hypoxia to induce glycolysis. In this study, we compared the metabolic characteristics of hypoxia-tolerant subterranean Gansu zokors under hypoxic conditions with those of hypoxia-intolerant Sprague-Dawley rats with a similar-sized surface area. We exposed Gansu zokors and rats to hypoxia I (44 h at 10.5% O2) or hypoxia II (6 h at 6.5% O2) and then measured the transcriptional levels of mTORC1 downstream targets, the transcriptional and translational levels of glycolysis-related genes, glucose and fructose levels in plasma and brain, and the activity of key glycolysis-associated enzymes. Under hypoxia, we found that hif-1α transcription was upregulated via the mTORC1/eIF4E pathway to drive glycolysis. Furthermore, Gansu zokor brain exhibited enhanced fructose-driven glycolysis under hypoxia through increased expression of the GLUT5 fructose transporter and ketohexokinase (KHK), in addition to increased KHK enzymatic activity, and utilization of fructose; these changes did not occur in rat. However, glucose-driven glycolysis was enhanced in both Gansu zokor and rat under hypoxia II of 6.5% O2 for 6h. Overall, our results indicate that on the basis of glucose as the main metabolic substrate, fructose is used to accelerate the supply of energy in Gansu zokor, which mirrors the metabolic responses to hypoxia in this species.